1959
DOI: 10.1002/srin.195903041
|View full text |Cite
|
Sign up to set email alerts
|

Ausscheidungsvorgänge in austenitischen Chrom‐Nickel‐Stählen und ihr Einfluß auf die Neigung zur interkristallinen Korrosion

Abstract: Licht‐ und elektronenoptische Gefügeuntersuchungen an austenitischen Chrom‐Nickel‐Stählen über den Einfluß des Lösungsglühens und einer nachfolgenden Anlaßbehandlung bis zu 10 000 h bei 450 bis 800° C auf Ausscheidungsvorgänge und ihre Beziehung zur interkristallinen Korrosion. Auswirkung eines Zusatzes von Niob und Tantal. Deutung der Zeit‐Temperatur‐Kornzerfall‐Schaubilder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

1960
1960
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Bäumel found that the precipitation of chromium carbides at tempering temperatures above 450 °C greatly reduces the corrosion resistance . These results support the theory of chromium depletion, which states that chromium is depleted from the surrounding metal matrix during the formation of chromium carbides . Before tempering, chromium is distributed homogeneously in the martensitic matrix.…”
Section: Introductionsupporting
confidence: 61%
“…Bäumel found that the precipitation of chromium carbides at tempering temperatures above 450 °C greatly reduces the corrosion resistance . These results support the theory of chromium depletion, which states that chromium is depleted from the surrounding metal matrix during the formation of chromium carbides . Before tempering, chromium is distributed homogeneously in the martensitic matrix.…”
Section: Introductionsupporting
confidence: 61%
“…The establishment and evaluation of intergranular corrosion (TTC) diagrams are discussed by Zitter [128], Wiester, Schuller and Schwaab [202] and Rocha [203]. From the very comprehensive body of literature now available on the intergranular corrosion of stainless steels, we shall only mention some of the basic works.…”
Section: Carbide Precipitations In Stainless Steels With Special Consmentioning
confidence: 99%
“…The corrosion and precipitation behaviour of stabilized austenitic stainless steels has been the subject of numerous investigations by Wiester and Pier [200], Wiester, Schuller and Schwaab [202], Rocha [203], Ruttmann, Gerlach and Kautz [52], Bungardt and Lennartz [221,222,223] and Bungardt, Lennartz and Wetzlar [224]. Herbsleb, Schuller and Schwaab [201] investigated a possible correlation between carbide and nitride precipitation and their effect on intergranular corrosion attack of titanium and niobium stabilized steels.…”
Section: Influence Of Titanium and Niobiummentioning
confidence: 99%
See 1 more Smart Citation
“…Da die Angaben in der Literatur sich ausschlieDlich auf austenitische Legierungen beziehen (5)(6)(7)(8), liegt der Verdacht nahe, daD es sich u m den EinfluD des Gefiiges handeln konnte, weil austenitische und ferritische Stahle sich in ahnlicher Weise auch hinsichtlich der interkristallinen Korrosion in waDrigen Medien unterscheiden. Bei der Reaktionstemperatur von 700 "C fur Salzschmelzenkorrosion werden namlich austenitische Stahle sensibilisiert (9), ferritische Stahle dagegen stabil gegliiht (…”
unclassified